COUNSELING OF HINDU RELIGION THROUGH PERFORMANCES TOPENG BONDRES ART - I Gusti Ngurah Ananjaya; , I Made Surada; I Nyoman Suarka (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
Counseling on Hinduism is carried out in many ways, such as through dharma wacana, dharma tula, dharma gita and others. But all that is currently rarely in demand. People prefer shows that are not serious and contain funny content. To address this, the government is trying to change its strategy by using Topeng Bondres (Bondres mask) as a medium. This Bondres is a kind of spectacle that contains more humorous elements so that people are interested in watching it. In order for the teachings of Hinduism to reach the people, these teachings are inserted in it along with funny things. If the teachings are taken seriously, people get bored quickly and quickly switch. Bondres masks have the usual communication style as people do so that they are more able to accept it. Rumors of Hindu teachings at the time of a funny appearance made people interested. Hindu teachings are accepted naturally and are not considered something to be afraid of. This work descriptively describes how Bondres masks are used as a medium for counseling Hindu religion. This media is said to be very effective in conveying Hindu religious teachings because people prefer entertainment than formal religious lectures.